EFFICACY OF EDUCATIONAL PROGRAM ON ANXIETY OF THE PATIENT UNDERGOING MAGNETIC RESONANCE SCAN - MR. BINIL ABRAHAM.; MR. SURESH SUKUMAR; DR. JOHNSON ALEX; MR. DAN ISAAC POTHIYIL (International Journal of Pharma and Bio Sciences, 2016)
Anxiety related issues are common for those who are undergoing for MRI scan. This may happen because of the anticipation about the Misaim is to study the efficacy of patient education program to reduce the anxiety of patients undergoing MRI scan. The Study Design is Randomized Controlled Trial. Three groups involved in this study are: (1) Intervention group (2) Placebo group (3) wait-listed group. Sample size: 25 patients in intervention and placebo group and 30 in wait-listed group. Tools used in the study: Anxiety Scale, Pulse Oximeter. Study Procedure: In this phase, data collection was done based on guidelines on randomized controlled trial. Sequence generation was done using a computer based program. Allocation concealment was achieved using Sequentially Numbered, Opaque, Sealed Envelopes (SNOSE) to avoid deciphering. The participants were blinded regarding the arm to which they were allocated. Informed Consent and socio-demographic data was obtained from the participant Comparison of the pre and post anxiety of patients in intervention and placebo group indicates that there is a significant decrease in anxiety levels of patients in intervention Compared to that of placebo group.Comparison of pre and post pulse of patients in intervention and placebo group indicates that there is no statistically significant change in the pulse readings. Comparsion of pre and post oxygen saturation level in patients in intervention and placebo group which indicates that there is no statistically significant change in the oxygen saturation level after intervention group as compared to placebo group.